Analisis Tingkat Kemandirian Belajar Siswa Pada Mata Pelajaran Fisika Kelas XII MAN 1 Batang Hari - Rizki Intan Sari (Department of Physics Education, Universitas Mataram, 2019)
This study aims to analyze the attitude of learning independence against learning physics for students of class XII MIA MAN 1 Batang Hari. This research uses quantitative research methods with descriptive statistical analysis techniques. The research sample uses a sampling technique that is total sampling. Total sampling is a sampling technique where the number of samples is equal to the population. The technique of collecting data is by submitting an instrument consisting of a questionnaire to a predetermined research sample. The results of this study indicate that the assessment of student independence is in the good category but some are not good.